Altered Local and Large-Scale Dynamic Functional Connectivity Variability in Posttraumatic Stress Disorder: A Resting-State fMRI Study - Fu, Shishun; Ma, Xiaofen; Wu, Yunfan; Bai, Zhigang; Yi, Yin; Liu, Mengchen; Lan, Zhihong; Hua, Kelei; Huang, Shumei; Li, Meng; Jiang, Guihua (Frontiers in Psychiatry, 2019)
Posttraumatic stress disorder (PTSD) is a psychiatric condition that can emerge after exposure to an exceedingly traumatic event. Previous neuroimaging studies have indicated that PTSD is characterized by aberrant resting-state functional connectivity (FC). However, few existing studies on PTSD have examined dynamic the changes in resting-state FC related to network formation, interaction and dissolution over time. In this study, we compared the dynamic resting-state local and large-scale FC between PTSD patients (n = 22) and healthy controls (HC) (n = 22) on (conducted as standard deviation in resting-state local and large-scale FC over a series of sliding windows). Local dynamic FC was examined by calculating the dynamic regional homogeneity (dReHo), and large-scale dynamic FC (dFC) was investigated between regions with significant dReHo group differences. For the PTSD patients, we also investigated the relationship between symptom severity and dFC / dReHo. Our results showed that PTSD patients were characterized by (I) increased dynamic (more variable) dReHo in left Precuneus (PCu); (II) increased dynamic (more variable) dFC between the left PCu and left insula; (III) decreased dFC between left PCu and left inferior parietal lobe (IPL), and decreased dFC between left PCu and right PCu. However, there is no significant correlation between the clinical indicators and dReHo / dFC after the family-wise-error (FWE) correction. These findings provided the initial evidence that PTSD is characterized by aberrant patterns of fluctuating communication within brain system such as the default mode network (DMN) and among different brain systems such as the salience network and the DMN.